Enhancing Myoblast Fusion and Myotube Diameter in Human 3D Skeletal Muscle Constructs by Electromagnetic Stimulation - Terrie, Lisanne; Burattini, Margherita; Van Vlierberghe, Sandra; Fassina, Lorenzo; Thorrez, Lieven (Frontiers in Bioengineering and Biotechnology, 2022)
Skeletal muscle tissue engineering (SMTE) aims at the in vitro generation of 3D skeletal muscle engineered constructs which mimic the native muscle structure and function. Although native skeletal muscle is a highly dynamic tissue, most research approaches still focus on static cell culture methods, while research on stimulation protocols indicates a positive effect, especially on myogenesis. A more mature muscle construct may be needed especially for the potential applications for regenerative medicine purposes, disease or drug disposition models. Most efforts towards dynamic cell or tissue culture methods have been geared towards mechanical or electrical stimulation or a combination of those. In the context of dynamic methods, pulsed electromagnetic field (PEMF) stimulation has been extensively used in bone tissue engineering, but the impact of PEMF on skeletal muscle development is poorly explored. Here, we evaluated the effects of PEMF stimulation on human skeletal muscle cells both in 2D and 3D experiments. First, PEMF was applied on 2D cultures of human myoblasts during differentiation. In 2D, enhanced myogenesis was observed, as evidenced by an increased myotube diameter and fusion index. Second, 2D results were translated towards 3D bio-artificial muscles (BAMs). BAMs were subjected to PEMF for varying exposure times, where a 2-hour daily stimulation was found to be effective in enhancing 3D myotube formation. Third, applying this protocol for the entire 16-day culture period was compared to a stimulation starting at day 8, once the myotubes were formed. The latter was found to result in significantly higher myotube diameter, fusion index, and increased myosin heavy chain 1 expression. This work shows the potential of electromagnetic stimulation for enhancing myotube formation both in 2D and 3D, warranting its further consideration in dynamic culturing techniques.